2015
DOI: 10.1007/s00296-015-3313-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rheumatoid arthritis on household chores and leisure-time activities

Abstract: The aim of the study was to determine household chores and leisure-time activities most affected by rheumatoid arthritis (RA) and to evaluate the perceived impact on performing these activities. Also, our aim was to estimate the required and received assistance for household chores. In an interview study via telephone, 124 patients with moderate-to-severe RA, visiting a tertiary-level dermatological clinic, listed spontaneously without predefined list the household chores and leisure-time activities that they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 31 publications
1
21
0
4
Order By: Relevance
“…A study in USA reported that the rate of work disability was more than 25%, after 10 years with RA . Higher rates were reported in European countries . In a Finnish study, it was reported that most female RA patients (≅84%) had difficulty performing household activities and more than 50% required assistance .…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…A study in USA reported that the rate of work disability was more than 25%, after 10 years with RA . Higher rates were reported in European countries . In a Finnish study, it was reported that most female RA patients (≅84%) had difficulty performing household activities and more than 50% required assistance .…”
Section: Discussionmentioning
confidence: 92%
“…29 Higher rates were reported in European countries. 27 In a Finnish study, it was reported that most female RA patients (≅84%) had difficulty performing household activities and more than 50% required assistance. 28 Another study reported that other family members may spend up to 7 hours in performing household activities if the female member of the family such as mother or wife has RA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations